The effects of oocyte donor and recipient body mass index on live birth rates and pregnancy outcomes following assisted reproduction - Jiaxin Xu, M.P.H; Heather S. Hipp, M.D; Sarah M. Capelouto, M.D; Zsolt P. Nagy, M.D., Ph.D; Daniel B. Shapiro, M.D; Jessica B. Spencer, M.D., M.Sc; Audrey J. Gaskins, Sc.D (Elsevier, 2021)
Objective: To investigate the effects of oocyte donor and recipient body mass index (BMI) on outcomes of vitrified donor oocyte assisted reproductive technology (ART). Design: Retrospective cohort study. Setting: Private fertility center. Patient(s): A total of 338 oocyte donors and 932 recipients who underwent 1,651 embryo transfer cycles in 2008-2015. Intervention(s): Multivariable log binomial regression models with cluster-weighted generalized estimating equations were used to estimate the adjusted risk ratios. Main Outcome Measure(s): Live birth, defined as the delivery of at least one live-born infant, including all embryo transfer cycles. Secondary outcomes included birth weight and gestational length only among singleton live births. Results: The mean ± SD body mass indexes (BMIs) of donors and recipients were 22.6 ± 2.5 kg/m2 and 24.6 ± 4.8 kg/m2, respectively. There were no significant associations between donor BMI and probability of live birth. Recipients with BMI ≥35 kg/m2 had a significantly higher probability of live birth compared with normal-weight recipients. Among singleton live births, recipients with BMI <18.5 kg/m2 had a lower risk whereas women with BMI ≥35 kg/m2 had a higher risk of delivery in an earlier gestational week compared with normal weight women. Recipients with a BMI ≥35 kg/m2 also had a higher risk of having a low birth weight infant compared with normal-weight women. Conclusions: In the setting of vitrified donor oocyte ART, recipient BMI was positively associated with probability of live birth but negatively associated with gestational length and birth weight among singleton births.